Talent development in natural science in elementary school: A juxtaposition of research and practice. (August 2021) - Mack, Elena; Breit, Moritz; Krischler, Mireille; Gnas, Jessica; Preckel, Franzis
Abstract: We present a working theory of person-related predictors of talent development in natural science during elementary school. The working theory resulted from the juxtaposition of scientific findings and teachers' expertise. The results showed that both teachers and researchers conceive of talent development in natural science as a complex process including abilities, personality traits, and skills as predictors. However, teachers focused mainly on skills whereas the scientific literature emphasized cognitive abilities. The working theory can be used for the identification and promotion of natural science talent and the development of teachers' diagnostic skills to assess students' potential in natural science. Highlights: The teacher's perspective is rarely considered when developing working theories of talent development. We identified important predictors of natural science talent development through an extensive literature search. We compared teacher contributions with the scientific findings to reach a common working theory. Teachers and researchers share a multidimensional and dynamic understanding of natural science talent.